2015
DOI: 10.1155/2015/392471
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of One Adipokine Nampt/Visfatin Suppresses the Inflammatory Stress‐Induced NF‐κB Activity and Affects Nampt‐Dependent Cell Viability in Huh‐7 Cells

Abstract: Nampt/visfatin acts in both intracellular and extracellular compartments to regulate multiple biological roles, including NAD metabolism, cancer, inflammation, and senescence. However, its function in chronic inflammation and carcinogenesis in hepatocellular carcinoma (HCC) has not been well-defined. Here we use Huh-7 hepatoma cells as a model to determine how Nampt/visfatin affects cellular survival under oxidative stress. We found that the transition of Nampt/visfatin from intracellular into extracellular fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Our study has a few limitations. Visfatin, as a form of extracellular NAMPT, is susceptible to overexpression under oxidative stress in HCC cells; it then inhibits the growth of hepatoma cells [ 34 ]. In contrast, Buldak et al [ 30 ] observed that elevated visfatin levels induced antioxidant capacity and promoted melanoma cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has a few limitations. Visfatin, as a form of extracellular NAMPT, is susceptible to overexpression under oxidative stress in HCC cells; it then inhibits the growth of hepatoma cells [ 34 ]. In contrast, Buldak et al [ 30 ] observed that elevated visfatin levels induced antioxidant capacity and promoted melanoma cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, AMPK is a key sensor of ATP resources in the cell, and is essential for rhythmicity of NAMPT in WAT. Furthermore, the ratio NAD+/NADH determines the production of reactive oxygen species (ROS), and oxidative stress increases NAMPT release (Lin et al 2015;Lu et al 2019). Consequently, NAMPT inhibition induces susceptibility to oxidative stress (Hong et al 2016;Xu et al 2017).…”
Section: Nampt Retains More Rhythmicity Than the Core Clock After Scn Lesionsmentioning
confidence: 99%
“…Indeed, this hypothesis is strengthened by observations that similar stress conditions, including ischaemia (Jing et al , ) and oxygen–glucose deprivation (OGD), strongly increase eNAMPT release in neurons and glial cells (Zhao et al , ) as well as hypoxia in melanoma cells (Grolla et al , ). Similarly, oxidative and endoplasmic reticulum (ER) stress also appear to increase eNAMPT release (Huh‐7 cells) (Pillai et al , ; Lin et al , ). These observations also remain to be systematically investigated.…”
Section: Introductionmentioning
confidence: 99%